Effect of hydrophilicity on fouling of an emulsified oil wastewater with PVDF/PMMA membranes - Ochoa, Nelio Ariel (2003)
Membranes with different degrees of hydrophilicity were prepared from PVDF and PMMA. The hydrophilicity was determined by using the contact angle technique. The distribution of pore radius was obtained from polydispersed solute permeation, scanning electron microscope (SEM) and hydraulic permeability. A higher hydrophilic character with the increase of PMMA in the casting solution and the appearance of larger macrovoids in the porous substructure were found without a substantial modification of the selective surface structure. However, a significant effect of compaction was evidenced due to the transmembrane pressure on membranes with high content of PMMA. An effluent from an engine factory was used to study the ultrafiltration performance of the prepared membranes. These assays show that membranes with a higher content of PMMA lead to a lower fouling.